Decoupling of the phase transitions and its effect on the magnetocaloric properties of Heusler alloys. (November 2021) - Agbo, Sunday Arome; Bhatt, Subhash; Khan, Mahmud
Abstract: The phase transitions and associated magnetic entropy changes in the Ni2 Mn0.70 Cu0.30 Ga Heusler alloy have been investigated. A tetragonal crystal structure was observed at room temperature, and upon heating, the material exhibited a partially coupled first order magnetostructural martensitic phase transition near 345 K. The coupling of the magnetic and structural phase transitions enhanced during cooling, which was evident in the large variation in the magnetocaloric properties of the material when the measurements were done while heating and cooling. For a field change of 50 kOe, the peak magnetic entropy change obtained while heating was −17 J kg −1 K −1 . Interestingly, the peak value was −33 J kg −1 K −1 when the measurements were done while cooling from 400 K to lower temperatures. The phase transitions were accompanied by sharp anomalies in the electrical resistivity of the material. The experimental results indicated that the magnetocaloric properties of Heusler alloys may be precisely controlled by manipulating the overlap of the first order martensitic and the second order ferromagnetic phase transitions. Highlights: Phase transitions and magnetic entropy changes in Ni2 Mn0.70 Cu0.30 Ga with a tetragonal crystal structure are reported. A partially coupled first order magnetostructural martensitic phase transition near 345 K has been observed. . Peak magnetic entropy changes of −17 J kg −1 K −1 (warming) and -33 J kg −1 K −1 (cooling) have been observed. The magnetic entropy changes can be optimized by controlling the overlap of the structural and magnetic phase transitions.